DOI: 10.11606/t.6.2021.tde-09032021-095532
|View full text |Cite
|
Sign up to set email alerts
|

Promoção da alimentação saudável no ambiente escolar: avaliação do Programa Horta Educativa em escolas estaduais de São Paulo

Abstract: the implementation of gardens in public schools and public children's centers. The school garden has proved to be an excellent strategy for food and nutrition education that enables a participatory pedagogical approach, articulating health, food and the environment. Objective-To evaluate SGP as a device for the promotion of adequate and healthy food (PAHF) in the school environment. Methodology-This is a qualitative study of evaluation by triangulation of methods, which evaluated SGP in state schools in the ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In Canada, the identified sustainability practices ( n = 2) involved school gardens, purchase of local and organic foods, participation in programs that promote closer ties between schools and local farmers, waste reduction, and the use of vegetarian dishes [ 24 , 71 ]. In Brazil, the only country in Latin America in which studies were identified ( n = 7), the most cited practices were related to school gardens [ 14 , 45 , 74 , 75 , 79 ] and educational activities for sustainability, including training for those involved in the operationalization of the National School Feeding Program (PNAE) [ 14 , 68 , 74 , 79 ]. However, the studies also cited activities to reduce waste [ 14 , 45 , 75 ], use of local [ 14 ] and regional [ 62 ] foods, partnerships for the development of sustainability activities (such as environmental preservation), and to encourage both the use of organic food and to value the work of those involved in all food production [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canada, the identified sustainability practices ( n = 2) involved school gardens, purchase of local and organic foods, participation in programs that promote closer ties between schools and local farmers, waste reduction, and the use of vegetarian dishes [ 24 , 71 ]. In Brazil, the only country in Latin America in which studies were identified ( n = 7), the most cited practices were related to school gardens [ 14 , 45 , 74 , 75 , 79 ] and educational activities for sustainability, including training for those involved in the operationalization of the National School Feeding Program (PNAE) [ 14 , 68 , 74 , 79 ]. However, the studies also cited activities to reduce waste [ 14 , 45 , 75 ], use of local [ 14 ] and regional [ 62 ] foods, partnerships for the development of sustainability activities (such as environmental preservation), and to encourage both the use of organic food and to value the work of those involved in all food production [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The involvement with school gardens and education activities for sustainability represented the most commonly reported practices, being identified in 36% ( n = 18) [ 14 , 20 , 24 , 43 , 45 , 46 , 50 , 51 , 55 , 59 , 60 , 61 , 64 , 66 , 74 , 75 , 78 , 79 ] and 28% ( n = 14) [ 14 , 20 , 35 , 44 , 51 , 53 , 56 , 57 , 59 , 60 , 61 , 69 , 74 , 79 ] of the studies, respectively. Among the studies that described the use of school gardens, 8% ( n = 4) [ 14 , 45 , 61 , 75 ] described the cultivation of organic foods and, in the context of education practices for sustainability, travel field studies [ 59 , 60 ] and cooking activities [ 14 , 20 , 44 , 69 ] were also cited.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the only country in Latin America in which studies were identified (n = 7), the most cited practices were related to school gardens [14,45,74,75,79] and educational activities for sustainability, including training for those involved in the operationalization of the National School Feeding Program (PNAE) [14,68,74,79]. However, the studies also cited activities to reduce waste [14,45,75], use of local [14] and regional [62] foods, partnerships for the development of sustainability activities (such as environmental preservation), and to encourage both the use of organic food and to value the work of those involved in all food production [68].…”
Section: Studies Characteristicsmentioning
confidence: 99%